Perjanjian Sewa Menyewa yang Dibuat di Hadapan Notaris Kaitannya dengan Putusan Hakim Mahkamah Agung - Heru Guntoro (Jurnal Hukum IUS QUIA IUSTUM, 2012)
An agreement shall be binding upon the parties, and each party is obliged to be responsible for what is stated in the agreement. This research focuses on the legal perspective of a lease agreement made before a notary public and its relation to the decision of Supreme Court Justice. The study uses normative, philosophical, juridical analysis; in addition, it is a qualitative, comparative research. During the study, a library research is conducted and legal materials are analyzed qualitatively using a case approach. The research leads to a conclusion that, first, a lease agreement made before a notary public is legal and authentic, and second, the decision of Supreme Court strengthens the lease agreement made before a notary public, and the Notary Deed is validated and inviolable.